The Relationships between Big Five Personality Traits and Subjective Vitality - Deniz, M. Engin; Satici, Seydi Ahmet (UNIV MURCIA, 2017)
The current study examined the relationship between big five personality traits and subjective vitality. Participant were 307 university students [180 ((59%)) female, 127 ((41%)) male, M-age = 21.24 years, SD = 1.21] who completed questionnaires package the Adjective Based Personality Scale and the Subjective Vitality Scale. A hierarchical regression analyses was used with big five personality traits to explain variance in subjective vitality. The results showed that extraversion, agreeableness, and openness were significant positive predictors and neuroticism was significant negative predictor of subjective vitality which accounted for 31% of the total variance. Consciousness did not significant predictor of subjective vitality. The significance and limitations of the results are discussed.
Keywords: Big Five personality; Subjective vitality; Hierarchical regression; Turkey; 5-FACTOR MODEL; SELF-DETERMINATION; LIFE SATISFACTION; Psychology